EFEKTIFITAS PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA POWER POINT TERHADAP KOMPETENSI BELAJAR SISWA DI KELAS XI MIA SMA NEGERI 1 PADANG BOLAK - lubis, adi israyadi; Siregar, Dedes Asriani; Sari, Lia Purnama (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2020)
Abstract This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model assisted by power point media on the learning competence of business and energy material students in Class XI MIA. This research was conducted using a quasi-experimental method with two group pretest-posttest design. The population in this study were all students of class XI consisting of 4 classes with a total of 128 students. The sampling technique used was simple random sampling technique, so the sample in this study was class XI MIA1 as an experimental class and class XI MIA2 as a control class totaling 70 students. Based on data analysis obtained: (1) student learning outcomes of business material and energy class XI before the application of Power Point Contextual Teaching and Learning (CTL) models assisted by power point media obtained an average score of 59.02 in the